Adsorption removing various basic nitrogen compounds from model diesel over allochroic silica gel - Xin Hong; Yunhe Li; Chang Gao; Yonghua Zhao; Ke Tang (Adsorption Science & Technology)
The adsorption removal of quinoline from model diesel by using alumina, diatomite, silica gel, and allochroic silica gel as adsorbents was investigated. The experiment results indicated that the adsorption denitrogenation performance of allochroic silica gel was more superior to other three adsorbents. The silica gel and allochroic silica gel were confirmed by characterization with X-ray diffraction, nitrogen adsorption–desorption, and ammonia temperature programmed desoption (NH 3 -TPD). X-ray diffraction results indicated that both the samples were amorphous structures. The average pore diameters of silica gel and allochroic silica gel were 18.46 and 1.80 nm, the Brunauer–Emmett–Teller surface areas were 437.86 and 623.39 m 2 /g, and the pore volumes were 0.9724 and 0.3442 cm 3 /g, respectively. The results of TPD showed that the acidity of allochroic silica gel was far stronger than that of silica gel which greatly enhanced its adsorption denitrogenation performance. The adsorption denitrogenation performance of allochroic silica gel for quinoline, aniline, and pyridine from model diesel was as follows: aniline, pyridine, and quinoline. Adsorption temperature, particle size, and arenes added in model diesel had little impact on the removal of aniline and pyridine except quinoline. The adsorbent-to-oil ratio had significant effects on adsorption denitrogenation, especially for quinoline. The N–Co bond between Co in allochroic silica gel and N atom in the basic nitrogen compounds molecule played a significant role. Furthermore, the allochroic silica gel could be easily regenerated by its adsorption denitrogenation performance for quinoline and pyridine by using calcination once or several times, except aniline. The adsorption isotherm results revealed that the adsorption of pyridine and aniline belonged to the Langmuir–Freundlich binding model, but the adsorption of quinoline belonged to Freundlich model.